Early Chirstian Judaism and Christian Gnosis, and their relation to emerging mainstream Christianity - Luttikhuizen, G. (Neotestamentica, 1994)
The first part of this paper discusses various forms of Christian Judaism and their relationship to lawfree Christianity. It is argued that it was on the basis of Luke-Acts that the Church Fathers were able to condemn Christian Jews as sectarians who had turned away from the original apostolic truth. The second part tries to explain why Gnostic philosophers were interested in the biblical stories about the creation of man and the early history of humankind, why Christians felt attracted to Gnostic mythological stories and their apparent distortions of Old Testament scripture, and why they were prepared to present the Gnostic myth of origins as the definitive truth revealed by Jesus Christ. It concludes with a few observations concerning the relationship between Gnostic and non-Gnostic Christians and their eventual separation.